AB1038 High Costs for Health System of Misdiagnosing Osteoarthritis as Rheumatoid Arthritis. (15th July 2016) - Buitrago-Garcia, D.; Castro, C.; Santos-Moreno, P.; Villarreal, L.; Ballesteros, G.; Bello, J.; Castillo, E.; Giraldo, R.; Gomez, D.; Aza, A.; Lopez, A.; Cardozo, A.; et al.
Abstract : Background: There are an important number of patients with osteoarthritis (OA) that are misdiagnosed as rheumatoid arthritis (RA) in general practice in Colombia. They are treated as such with disease modifying anti-rheumatic drugs (DMARDs), leading to higher economic costs for health system. Objectives: The aim of this study was to calculate the possible direct economic costs of the care of OA patients misdiagnosed as RA in a 48 month period in a cohort of patients derived to a specialized RA center in Colombia. Methods: A descriptive cross sectional study was performed. Patients derived during a 48 month period to a RA specialized center with presumptive diagnosis of this disease and found finally diagnosed with OA were included in analysis. Each patient was evaluated to confirm or rule-out diagnosis of RA as follows: a rheumatologist fulfilled a complete medical record, including joint counts; it was assessed rheumatoid factor and anti-citrullinated antibodies, and other laboratories depending on each case. Also were made x-rays of hands and feet, and in some cases of persistent doubt about the diagnosis was requested comparative MRI of hands or/and feet. Then we described the direct costs of care in Colombian pesos (COP) of these false-positive RA patients assuming an average of 4 visits/year to general practitioner (8.400 COP/medical appointment), 2 visits/year for physiatrist and orthopedics (33.995 COP/ medical appointment) and 4 set/year of conventional laboratories (92.161 COP/set). Cost of medication doses were calculated for an average use of methotrexate, sulfasalazine, chloroquine and prednisolone (200.840 COP/monthly). Indirect costs were not calculated. Results: We found 2930 OA patients misdiagnosed as RA in a period of 48 months. For each patient we calculated 33.600 COP/year for general practitioner visits, 135.980 COP/year for specialized medicine visits, 368.644 COP/year for laboratory sets and 2.431.248 COP/year for medications. This leads to a total cost of 2.969.472 COP/year per patient. Given a total of 2930 misdiagnosed patients cost rise to 8.700.552 million COP/year (2, 900, 184 US dollars/year). Conclusions: There is an important economic implication of the misdiagnosis of OA as RA, being this the most frequent mistake in the diagnosis of this disease. The implementation of educational programs for health care primary physicians and specialized RA centers where a process of screening diagnosis is made could save this amount of money for the health system in Colombia. Disclosure of Interest: None declared